Maturation of 'Baigent' apples protected by anti-hail nets and sprayed with aminoethoxyvinylglycine and ethephon - Soethe, Cristina (2022)
The objective of this work was to evaluate the effect of pre‑harvest spraying with aminoethoxyvinylglycine (AVG) and ethephon on fruit maturation of 'Baigent' apple (Malus domestica) trees grown under black anti‑hail nets. The treatments were: control; 125 mg L-1 AVG, sprayed 30 days before anticipated harvest time (DBAH); 120 mg L-1 ethephon 7 DBAH; 62.5 mg L-1 + 62.5 mg  L-1 AVG 30 and 20 DBAH; and 62.5 mg L-1 + 62.5 mg L-1 AVG 30 and 20 DBAH + 120 mg L-1 ethephon 7 DBAH. Fruit were harvested in the commercial harvest of the control treatment (harvest 1) and 14 days later (harvest 2). Yellowing and loss of firmness were delayed by the treatments with AVG and accelerated by that with ethephon. AVG application in a single rate of 125 mg L-1 30 DBAH or in two split rates of 62.5 mg L-1 30 and 20 DBAH delays fruit maturation. The pre-harvest application of AVG in a single rate reduces the red color of the fruits, which is not affected by application in split rates, combined or not with ethephon, regardless of the date of harvest.